Colorimetric Parameters and Pigments Content in Five Different Peel Colors of Feijoa Fruit [Acca sellowiana (Berg) Burret] - Zaccari, Fernanda; Del Puerto, Marta; Vignale, Beatriz; Pritsch, Clara (Agrociencia Uruguay, 2017)
The aim of this study was to characterize five guava fruit peel color on a visual scale used in the selection and breeding of this species in Uruguay by the colorimetric parameters in the CIELAB color space and measure total chlorophyll, chlorophyll a, chlorophyll b and total carotenoids content. The visual scale analyzed the skin colour ranked of Yellow (A), Green (AV) Green Yellow (VA), Green (V) and Green Green (VV). The brightness and saturation of the skin fruit colour, lowered by increasing the green colour of the visual scale (L* 57.2 to 36.4, Cab* 41.4 to 15.9). The tones were 90.4 to 121.3 ºhab coincident with perceived in the skin visual scale colour categories A to VV. The color difference between categories of visual scale was easily differentiated by a non-expert observer. The color index statistically discriminated the five skin colour which values were 0 (A) -4 (AV), -5 (VA), -12 (V) and -17 (VV). The total chlorophyll content (0.160 to 0.119 mg g-1 fresh weight) and 0.085 to 0.362 mg g-1 fresh weight chlorophyll a, was positively correlated with the colours toward skin greenish- (r = 0.56 and 0.80; p ≤ 105). Instead, total carotenoids (0.043 to 0.119 mg g-1 fresh weight) had low relation with the visual scale (r = -0.03; p 0.225), probably masked for chlorophylls, also with the highest content in skin VV fruits.